Ground improvement for coastal engineering - Takahashi, Hidenori (CRC Press, 2023)
This practical guide covers the investigation, design, and execution of ground improvement in coastal areas. It explains how to decide whether ground improvement is necessary, which method to choose, and how to design and execute it. The book introduces various ground improvement technologies including seismic reinforcement and liquefaction countermeasures and addresses the measures to be taken to sustain ground against external forces. Reliable Japanese ground improvement technologies are presented as well as the latest BIM/ICT technology used in their execution. The book suits professionals in the ground improvement industry, especially geotechnical designers and contractors